2019
DOI: 10.1021/acs.joc.8b03242
|View full text |Cite
|
Sign up to set email alerts
|

Odorless Isocyanide Chemistry: One-Pot Synthesis of Heterocycles via the Passerini and Postmodification Tandem Reaction Based on the in Situ Capture of Isocyanides

Abstract: This paper reports the tandem reaction strategy of the Passerini/Staudinger/aza-Wittig reaction based on the in situ capture of isocyanides. According to this strategy, isocyanides are synthesized in situ and immediately work as the substrate for the Passerini reaction and postmodification tandem reaction in one pot. In addition, two types of new compounds, 5-oxo-3,5-dihydrobenzo­[e]­[1,4]­oxazepines and 6-oxo-5,6-dihydro-2H-1,4-oxazines, were synthesized using the tandem reaction strategy that includes five-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Later, Wang and co‐workers introduced a direct disulfide‐directed C─H activation for the synthesis of thiophenols from disulfide and arylboronic acid with oxygen as the oxidant . However, none of the previous methods for 2‐(phenylthio)phenol derivatives synthesis could achieve recycling of the catalyst . From the perspectives of sustainable development and easy recovery, it is clearly necessary to develop a recoverable catalytic system to realize the synthesis of 2‐(phenylthio)phenol derivatives with good efficiency and recyclability.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Wang and co‐workers introduced a direct disulfide‐directed C─H activation for the synthesis of thiophenols from disulfide and arylboronic acid with oxygen as the oxidant . However, none of the previous methods for 2‐(phenylthio)phenol derivatives synthesis could achieve recycling of the catalyst . From the perspectives of sustainable development and easy recovery, it is clearly necessary to develop a recoverable catalytic system to realize the synthesis of 2‐(phenylthio)phenol derivatives with good efficiency and recyclability.…”
Section: Introductionmentioning
confidence: 99%
“…Later, researchers found that OMS-2 also demonstrated an excellent performance in the field of organic synthetic catalysis when different metal ions were used to modify OMS. Reflux, [15][16][17][18] ball milling, 19 impregnation, 20 and multi-step hydrothermal methods [21][22][23] can produce OMS doped with Cu.…”
Section: Introductionmentioning
confidence: 99%
“…Small organic fluorophores are indispensible tools for the construction of fluorescent probes because of the controllable optical properties such as bodipy, coumarin, rhodamine, fluorescein, etc . Among them, fluorophores derived from benzothiazole are widely used as the dye platform for designing of fluorescent probes .…”
Section: Introductionmentioning
confidence: 99%